Tax measures to encourage entrepreneurship by cooperatives - Atxabal Rada, Alberto (REVESCO. Revista de Estudios Cooperativos, 2020)
Tax law has adopted in recent years some of measures to promote and encourage entrepreneurship, which are included in the regulations of the main direct taxes. On the other hand, among entrepreneurs, and among social entrepreneurs, there are cooperatives, no doubt. Therefore, cooperatives have the right to apply tax measures that encourage entrepreneurship, like any other entrepreneur. This work focuses on the analysis and criticism of tax regulations that encourage entrepreneurship and, at the same time, are applicable to cooperatives, or in other case, that are not applicable to cooperatives without any reason for the omission. We will study, therefore, tax measures that encourage entrepreneurship promoted by the cooperatives, foreseen in Spanish tax regulations, and we will focus on the analysis of the main direct taxes, as Corporation Income Tax and the Personal Income Tax, because both taxes collect most of the tax incentives for entrepreneurship in Spanish legislation. This last circumstance focuses us to remark the tax rules adopted in the Basque Country, which differ partially from the regulation of state laws. Thus, we observe that the tax treatment of entrepreneurship carried out by a cooperative is more generous in Basque regulation than in state regulations, although in both regulations there are fiscal rules to promote entrepreneurship not applicable to cooperatives, without acceptable justification.